A Review on Channel Allocation Schemes in Mobile Ad Hoc Networks (International Journal of Engineering and Computer Science, 2017)
Mobile Ad Hoc networks are the networks that has no centralized control in it. The Ad Hoc network consists of mobile nodes that exchange packets by sharing a common broadcast radio channel. Bandwidth that is available for communication to be shared is limited and thus there is a need to control the access to this shared medium. Due to this, bandwidth can be used very efficiently. In MANET’s, MAC layer protocol plays a very vital role in efficient utilization of shared media in a distributed manner. There are three contradicting requirements at the MAC layer and they are: maximize channel utilization, minimize control overhead and ensure fairness. In this paper, we have studied about channel allocation schemes in mobile communication and have also studied various reuse partitioning schemes, handoff’s effects.